Koncept mrežnega pomenskega slovarja slovenskih besed - Zupan, Jure (Jezik in slovstvo, 2009)
The article presents the possibility of linking words and looking them up according to meanings, which is not possible in printed dictionaries. The advantages and possibilities offered by a dictionary organised in this way are described and a working version of a network organised dictionary of Slovene words in computer accessible form is presented. The purpose of the network dictionary presented is to offer users information about individual words not only in the sense of lemmatisation (of a dictionary headword), in which not only the word class of the treated word is stated but also the semantically connected words of a broad and narrow meaning. In the described working version more than 5000 words are ordered in a semantic network, most of them nouns. The working version is available to users on a CD that can be obtained by interested readers from the author at his address.
Keywords: drevo odločitev; hierarhija pomenov; jezikoslovje; linguistics; mrežni slovarji; osebek/predmet; pomenske zveze; računalniški programi; Slovene; slovenski slovarji; slovenščina